Analysis of Students’ Speaking and Grammar’s Performance through Task Based Learning Approach - Mahulette, Astrid; Sasole, Ci Eda (MATAI: International Journal of Language Education, 2025)
This study explores the implementation of the Task-Based Learning (TBL) approach in enhancing the speaking ability and grammatical accuracy of first-semester students in the Department of Agricultural Socio-Economics, Faculty of Agriculture, Pattimura University. The research was motivated by students’ low motivation, limited English proficiency, and inadequate prior exposure to the language. Employing a qualitative case study design, data were collected through classroom observations, semi-structured interviews, and documentation of students’ presentations and discussions over eight meetings. Thematic analysis following Braun and Clarke’s framework revealed four major findings: (1) students initially demonstrated very low interest, motivation, and cognitive ability in English, (2) the implementation of TBL significantly improved students’ speaking fluency and grammatical accuracy, (3) several challenges emerged, including limited instructional time, inadequate learning facilities, and students’ anxiety when speaking English, and (4) supporting factors such as relevant teaching materials, contextual learning tasks, and a flexible, student-centered teaching approach contributed to the method’s success. The integration of communicative and grammar-focused tasks fostered a more engaging, collaborative, and meaningful learning atmosphere. Students who were initially passive became more motivated, confident, and active participants in class discussions. Despite time and resource constraints, TBL proved to be an effective pedagogical approach for non-English major students, particularly in contexts where English exposure is minimal. The study underscores the importance of adapting communicative, task-based methodologies to enhance English language learning in Eastern Indonesia’s higher education institutions, addressing both cognitive and affective domains of student development.